Analisis Dan Implementasi Sistem Informasi SDM menggunakan Sentrifugo di Pesantren Petik YBM PLN - Fauzi Hafsar; Rusmanto; Reza Aldiansyah (LPPM STT Terpadu Nurul Fikri, 2020)
Human Resources Information System (HRIS) is a utilization of Information Systems (IS) to help implementation of Human Resource Management. The Application of HR Management is used by Companies or Organizations in carrying out managerial functions such as managing employee data, evaluating employee performance, leave requests, service requests, and so on. Based on this, one of the Organizations namely Pesantren Information and Communication Technology Foundation Baitul Maal PLN (Pesantren PeTIK YBM PLN) wants to take advantage of the SISDM application to assist the running of managerial functions in his organization.. The aim of research is analyzing the process of HR Management in Pesantren PeTIK before the implementation of HRIS using sentrifugo so that it gets improvement after implementing sentrifugo in Pesantren PeTIK. The study has involved the descriptive quantitative analysist methode, where the primary data source was from some interviews and questionnaires. After the implementation of Sentrifugo, it is expected that the HRIS would be enhanced and transformed from manual to digitally centralized. Referring to the results of the research, there is a need to conduct further research on the implementation of sentrifugo at Islamic Boarding school of PeTIK (Pesantren PeTIK).